2008
DOI: 10.1182/blood-2007-12-126987
|View full text |Cite
|
Sign up to set email alerts
|

Absence of donor Th17 leads to augmented Th1 differentiation and exacerbated acute graft-versus-host disease

Abstract: Th17 is a newly identified T-cell lineage IntroductionAcute graft-versus-host disease (GVHD), the leading cause of morbidity and mortality of allogeneic hematopoietic cell transplantation (HCT), is a complex process involving dysregulation of inflammatory cytokine cascades and distorted donor cellular response against host alloantigens. 1 Activation of alloreactive donor T cells is initiated by host antigen-presenting cells (APCs), especially dendritic cells (DCs). [2][3][4][5] Much effort has been devoted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
184
4
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(201 citation statements)
references
References 59 publications
11
184
4
2
Order By: Relevance
“…Second, IL-17 produced by Th17 cells as they accumulate at the site of inflammation may negatively regulate the recruitment of Th1 cells. Consistent with the notion of a feedback loop in which IL-23 and IL-17 negatively regulate the IL-12/IFN-␥ network, the administration of an anti-IL-17 mAb worsens the course of dextran sodium sulfate-induced colitis, the elimination of IL-23 worsens the development of T cell-mediated trinitrobenzene sulfonic acid-induced colitis, and donor Th17 cells negatively regulate Th1 differentiation and ameliorate acute graftvs-host disease (51)(52)(53). Similarly, in a mouse model of allergic asthma, IL-17 functions as a negative regulator by repressing expression of the eosinophil chemokine CCL11 (eotaxin) and the Th2 chemokine CCL17 (thymus-and activation-regulated chemokine or TARC) (27).…”
Section: Discussionmentioning
confidence: 57%
“…Second, IL-17 produced by Th17 cells as they accumulate at the site of inflammation may negatively regulate the recruitment of Th1 cells. Consistent with the notion of a feedback loop in which IL-23 and IL-17 negatively regulate the IL-12/IFN-␥ network, the administration of an anti-IL-17 mAb worsens the course of dextran sodium sulfate-induced colitis, the elimination of IL-23 worsens the development of T cell-mediated trinitrobenzene sulfonic acid-induced colitis, and donor Th17 cells negatively regulate Th1 differentiation and ameliorate acute graftvs-host disease (51)(52)(53). Similarly, in a mouse model of allergic asthma, IL-17 functions as a negative regulator by repressing expression of the eosinophil chemokine CCL11 (eotaxin) and the Th2 chemokine CCL17 (thymus-and activation-regulated chemokine or TARC) (27).…”
Section: Discussionmentioning
confidence: 57%
“…Several mouse model experiments have revealed that transfer of IL-17-producing cells induced acute GVHD, [33][34][35] whereas in contrast there is a report 31 showing that donor IL-17-producing cells ameliorated acute GVHD. Host DCs are critical in the initiation of acute GVHD, [52][53][54] leading to a hypothesis that IL-17-producing cells could modify the function of host DCs through unknown mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…[21][22][23][24][25][26][27][28][29] Moreover, several reports have so far shown that Th17 cells and IL-17 has a significant impact on the development of acute GVHD in mouse models. [30][31][32][33][34][35] Recent reports have shown association of SNPs in the IL-17 gene with autoimmune diseases such as rheumatoid arthritis and ulcerative colitis. [36][37][38][39] The promoter SNP of the IL-17 gene, rs2275913 (G197A), was found to be associated with the susceptibility of rheumatoid arthritis in the Norwegian population 38 as well as that of ulcerative colitis in the Japanese population.…”
Section: Introductionmentioning
confidence: 99%
“…The role of IL-17-producing Thelper cells is increasingly being recognized in GvHD. [63][64][65][66][67] Tournadre et al 68 recently showed by analyzing muscle biopsies of patients with inflammatory myopathies that IVIG could mediate their immunomodulation by acting on the Th17 pathway. One could speculate that IVIG exert their modulatory effect on GvHD by impairing the Th17 pathway, although more analysis on other Th17-family cytokines and on the nature of IL-17 secreting cells in our model will be required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%